If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-13=x-3/4
We move all terms to the left:
-13-(x-3/4)=0
We add all the numbers together, and all the variables
-(+x-3/4)-13=0
We get rid of parentheses
-x-13+3/4=0
We multiply all the terms by the denominator
-x*4+3-13*4=0
We add all the numbers together, and all the variables
-x*4-49=0
Wy multiply elements
-4x-49=0
We move all terms containing x to the left, all other terms to the right
-4x=49
x=49/-4
x=-12+1/4
| 5y-8=2(3y+2) | | 7x+4+7x=-8+2x-6+6x | | 76-49=g | | 13=2m+5. | | -26-4n=6n | | –2=3(s+18)+–11 | | 16-8=h | | 5+3x+6-14=124 | | Z^2i-8=0 | | -3-8y=-27 | | x4+8=32 | | 5d(d2-8)=2 | | -4+1b+6b=9+8+4b | | 0,32y=48 | | 5p=21+ | | b+40=6b | | 3x*5x=450 | | 124=14-6x+x3+5 | | 3z+18=2z-10 | | 3x×5x=450 | | 0.12(2a–5)+3a=81 | | ٥+٢(n+١)=٢n | | -2-2x=-6+8x | | 18-3c=42 | | 2b+8=3b-9 | | 91-42=g | | (5x-10)=(2.5x) | | 3y-15=2y+6 | | 8w-1=47 | | 39-17=p | | 2(x-1)+6=4x-2 | | -21=5+x |